Social and Labour Plans and wellbeing of South African mining communities - Letsoalo, Katlego (University of the Witwatersrand, Johannesburg, 2023)
The mining industry in South Africa has been instrumental to the developed of the economy however legacy issues were inherited by the Republic as a result of apartheid policy that existed and were key to the mining sector. A number of policies aimed at ensuring that the broader society and mining host communities benefit from mining activity were introduced by government. Despite the policies and initiatives implemented by mining companies and local government, these communities continue to protest due to lack of basic needs in these areas. This raises the question of whether development initiatives these communities are effective. The relationship between mining companies, communities and local government is captured in the MPRDA with a focus on Social and Labour plans (SLP). This relationship is explored using Sustainable Development Goals (SDGs) which apply to all countries and reflect universal goals and targets that define the global community's desire and opportunity towards a sustainable future. They study will using SDGs to optimal evaluate whether mining companies and local government have really improved the standard of living in these communities and the overall well-being
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Social and Labour Plan; Sustainable Development Goals; UCTD; SDG-11: Sustainable cities and communities